Thoracic Endoscopy : Advances in Interventional Pulmonology. - Simoff, Michael J. (John Wiley & Sons, 2008)
Written by some of the world's leading practitioners - and pioneers - in the field, Thoracic Endoscopy is the first up-to-the-minute, expert reference for clinicians with a solid foundation in diagnostic bronchoscopy and chest medicine needing to extend their clinical expertise in response to two decades of rapid development. Thoracic Endoscopy covers four key areas of practice:.:.; advanced diagnostic bronchoscopy.; the latest techniques for interventional bronchoscopy including the traditional rigid bronchoscopy techniques, ablative instruments and stents and a discussion of endobronchia.